Analysis of phenolic compounds in onion nectar by miniaturized off-line solid phase extraction-capillary zone electrophoresis - Soto Vargas, Verónica Carolina (2014)
Onion is an important vegetable crop which depends heavily on cross-pollinating insects for any significant increase in seed production. Nectar is the most important floral reward offered by plants. Minor components such as phenolic compounds in nectar affect bee foraging. A simultaneous determination of 4-vinylphenol, catechin, naringenin, rutin, cinnamic acid, syringic acid, chlorogenic acid, apigenin, vanillic acid, luteolin, quercetin, and caffeic acid in onion nectar lines by CZE-UV is reported. Limited nectar amounts make it difficult to apply the most commonly employed methods of extraction for phenolic compounds. Thus, the extraction of phenolic compounds in nectar was performed by solid phase extraction (SPE) using a home-made minicolumn packed with a suitable filtering material (C18, 50 mg) connected to a vacuum pump. Effects of several important factors affecting extraction efficiency as well as electrophoretic performance were investigated to acquire the optimum conditions. Under the proposed conditions, the analytes could be separated within 8 min in a 50 cm effective length capillary (75 μm ID) at a separation voltage of 25 kV in 30 mmol L-1 boric acid as BGE (pH 9.5). Sample results suggest that the phenolic composition has great influence on bee preference. Furthermore, the markedly qualitative and quantitative analytical differences in the phenolic profile of onion lines found in this study contribute to the understanding of the factors that affect onion pollination for hybrid seed production.